Pengembangan Modul Pembelajaran â€œDianaâ€ (Media Baca Anak) untuk Anak Cerebral Palsy - Assabilia, Nadhila Berlian; Iftayani, Itsna; Kusumastuti, Wanodya (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This developmental research aims to improve the reading ability of children with cerebral palsy. The study resulted in a learning module product called "Diana (Children's Reading Media)," which serves as a guidebook for using the developed flash card media. The learning module has been validated by experts to assess its feasibility. This developmental research employed the Research and Development (RnD) method by Borg and Gall, which was modified by Sugiyono, using five stages: (1) Potential and Problems, (2) Data Collection, (3) Product/Media Design, (4) Product/Media Validation, and (5) Media Revision. The research was conducted in two special needs schools (SLB) in Kebumen Regency and two SLBs in Purworejo Regency that provide educational services for children with cerebral palsy. Data analysis techniques in this study used qualitative analysis and descriptive quantitative analysis as the basis for improving the developed product. The result of this research is the Diana learning module (Children's Reading Media) for children with cerebral palsy. The feasibility level of the Diana learning module was assessed through material and media validation by experts. The overall average score from three material expert validators was 86%, which, in terms of qualification, is "Very Good" with the note "Highly feasible without revision." The overall average score from one media expert validator was 83%, which, in terms of qualification, is "Very Good" with the note "Highly feasible without revision." However, there were some inputs and suggestions from the validators that required the module to be revised. The conclusion from the material and media validation results is that the Diana learning module is feasible to be used as a learning module for children with cerebral palsy.